Care activism : migrant domestic workers, movement-building, and communities of care - Tungohan, Ethel (National Women's Studies Association/University of Illinois first book prize., 2023)
"Tungohan's project traces the arrival of migrant care workers in Canada beginning in the early twentieth century through to the contemporary age in which Filipina migrant care workers constitute nearly 95% of all live-in caregivers in the country. Within that timeline, the project concentrates more fully on the emergent migrant care worker activism which has led to institutional policy changes with both the Foreign Domestics Movement (FDM) and the Live-in Caregiver Program (LCP) -- programs that have placed strict terms on workers. Unlike other migrant worker groups, migrant care workers have been inordinately successful with their activism; besides policy changes, migrant care worker activism has created greater public awareness regarding the rights of migrant care workers, and has formed new organizations that meet the needs of migrant care workers in ways that sending and receiving states cannot or will not. Incorporating seven years of primary and archival research, Tungohan's project examines the types of organizing currently taking place among migrant care workers, the internal dynamics of such organizing, as well as the different activist sites, strategies, and short- and long-term goals that define migrant care worker activism. Through this specified focus on Canadian migrant care workers, Tungohan's project makes greater connections to the role migrant workers play in Western societies. Care activism challenges the stereotype of downtrodden migrant caregivers by showing that care workers have distinct ways of caring for themselves, for each other, and for the larger transnational community of care workers and their families. Ethel Tungohan illuminates how the goals and desires of migrant care worker activists goes beyond political considerations like policy changes and overturning power structures. Through practices of subversive friendships and being there for each other, care activism acts as an extension of the daily work that caregivers do, oftentimes also instilling practices of resistance and critical hope among care workers. At the same time, the communities created by care activism help migrant caregivers survive and even thrive in the face of arduous working and living conditions and the pains surrounding family separation. As Tungohan shows, care activism also unifies caregivers to resist society's legal and economic devaluations of care and domestic work by reaffirming a belief that they, and what they do, are important and necessary"--